2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942909
|View full text |Cite
|
Sign up to set email alerts
|

SLIP with swing leg augmentation as a model for running

Abstract: Abstract-Swing leg adjustment, repulsive leg function and balance are key elements in the control of bipedal locomotion. In simple gait models like spring-loaded inverted pendulum (SLIP), swing leg control can be applied to achieve stable running. The aim of this study is to investigate the ability of pendulum like swing leg motion for stabilizing running and reproducing a desired (human like) gait pattern. The employed running model consists of two sub-models: SLIP model for the stance phase and a pendulum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Also, the CoP excursion and the effective leg length may change when runners tend to land more on the fore-foot at higher speeds (Breine et al, 2014;Lai et al, 2020). Lastly, pendulum effects of the segmented swing-leg on stiffness should be considered (Clark et al, 2017;Kugler & Janshen, 2010;Maykranz & Seyfarth, 2014;Rashty et al, 2014). Together, this would result in a complex model to estimate leg stiffness.…”
Section: Vertical Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the CoP excursion and the effective leg length may change when runners tend to land more on the fore-foot at higher speeds (Breine et al, 2014;Lai et al, 2020). Lastly, pendulum effects of the segmented swing-leg on stiffness should be considered (Clark et al, 2017;Kugler & Janshen, 2010;Maykranz & Seyfarth, 2014;Rashty et al, 2014). Together, this would result in a complex model to estimate leg stiffness.…”
Section: Vertical Stiffnessmentioning
confidence: 99%
“…The swing leg motion is often ignored in SLIP models as they essentially describe the course of one step (technically a half-cycle). Rashty et al (Rashty et al, 2014) showed that by modelling the pendular motion of the swing leg in the conventional SLIP model, the generated momentum of the swing leg induces sequential steps. Consequently, the forward motion becomes more stable, which led the authors to suggest that the swing leg may help to reduce muscular force provided by the stance leg (Rashty et al, 2014).…”
Section: Leg Swingmentioning
confidence: 99%
“…Instead of Velocity based leg adjustment, a second approach which can be considered as a template based control method for leg swinging is to assume a passive pendulum-like movement of the swing leg (Knuesel et al, 2005 ; Mohammadinejad et al, 2014 ). Mochon and McMahon presented a model comprising a stiff stance leg and a segmented swing leg (Mochon and McMahon, 1980 ) which provides a better match of human walking dynamics, compared with the inverted pendulum model.…”
Section: Locomotor Sub-function Concept and Template Modelsmentioning
confidence: 99%
“…However, swing leg movement is still a missing part in SLIP based models. In Mohammadinejad et al ( 2014 ), we presented a new model combining SLIP for stance leg with pendulum movement for the swing leg in running. In this model the pendulum length is adapted at each step to attenuate any perturbation or error from desired movement.…”
Section: Locomotor Sub-function Concept and Template Modelsmentioning
confidence: 99%
See 1 more Smart Citation